COMPARATIVE ANALYSIS OF THE EFFICACY OF FIXED-DOSE COMBINATIONS OF AMLODIPINE/LISINOPRIL AND BISOPROLOL/HYDROCHLORTHIAZIDE IN PATIENTS WITH ESSENTIAL ARTERIAL HYPERTENSION COMBINED WITH OBESITY AND OVERWEIGHT - O. D. Ostroumova; A. I. Kochetkov; M. V. Lopukhina (Рациональная фармакотерапия в кардиологии)
Aim. To study the characteristics of the daily profile of blood pressure (BP) and heart damage in patients with essential hypertension (HT), depending on the presence of obesity as well as the antihypertensive and organoprotective effects of fixed-dose combinations of amlodipine/lisinopril and bisoprolol/hydrochlorothiazide in hypertensive patients with obesity or overweight.Material and methods. 60 patients with untreated HT, stage II, degree 1-2 (51.7% of men, aged 53.6±0.8 years) were examined. 24-hour BP monitoring and transthoracic echocardiography with calculation of myocardial stiffness parameters were performed in all patients. Hypertensive patients with obesity and overweight were randomized into groups treated with fixed-dose combinations amlodipine/lisinopril (n=25) or bisoprolol/hydrochlorothiazide (n=30). Doses of drugs were titrated until the target BP was achieved. The follow-up was 12 weeks.Results. Patients with HT and obesity (n=28) compared with hypertensive patients without obesity (n=32) had greater systolic BP (SBP) variability at night (p<0.05) and a morning surge in SBP (p<0.01), end systolic volume (p<0.05), systolic volume (p<0.01),right ventricle anterior-posterior dimension (p<0.001), right atrium volume (p<0.01), the thickness of the interventricular septum (p<0.01) and the posterior wall (p<0.001) of the left ventricle (LV), significantly lower LV global longitudinal systolic 2D-strain (p<0.001), coefficient of diastolic and end-systolic LV elastance (p<0.05 for both). At the end of the follow-up period patients in the amlodipine/lisinopril group compared to patients in the bisoprolol/hydrochlorothiazide group had a greater decrease in the mean daily pulse BP (-10.8 vs -5.4 mm Hg, respectively; p<0.05) and variability of SBP in daytime (-2.8±0.8 vs -0.9±0.3 mm Hg, respectively; p<0.05). Only patients in the amlodipine/lisinopril group had a significant decrease in the variability of SBP (from 12.2±0.8 to 10.9±0.5 mm Hg; p<0.05) and diastolic BP (from 9.3±0.5 to 8.4±0.4 mm Hg; p<0.001) at night. Patients in the amlodipine/lisinopril group compared to patients in the bisoprolol/hydrochlorothiazide group had a greater increase in the left atrium strain (p<0.01), 2D-strain of LV and a greater decrease in the LV end diastolic stiffness (-21.39±2.45 vs -3.54±1.57 mm Hg/ml, respectively; p<0.001), the LV end systolic elastance (-16.15±2.14 vs -12.85±1.37 mm Hg/ml, respectively; p<0.05), and LV myocardial mass index (-13.2±0.9 vs -8.4±0.7 g/m2, respectively; p<0.01), the thickness of the interventricular septum and the posterior wall of the LV.Conclusion. Untreated hypertensive obese patients in comparison with hypertensive patients without obesity have higher BP level variability during the night and early morning SBP surge, greater sizes of the heart chambers and LV myocardial wall thickness, higher LV myocardium stiffness. In obese or overweight patients with HT, a fixed-dose combination of amlodipine/lisinopril, compared with the fixed-dose combination of bisoprolol/hydrochlorothiazide, resulted in a more significant decrease in pulse BP and variability of systolic and diastolic BP at night, contributed to a more pronounced improvement in the elastic properties of the left atrium and LV myocardium and decrease in LV hypertrophy.